Acute Ethanol Reduces Reversal Cost in Discrimination Learning by Reducing Perseverance in Adolescent Rhesus Macaques. (8th January 2013) - Wright Jr, M. Jerry; Glavis‐Bloom, Courtney; Taffe, Michael A.
<x xml:space="preserve">Abstract</x> Background Acute alcohol exposure produces cognitive deficits in adults but less is known about the acute cognitive effects of alcohol in adolescents. The cognitive impact of acute alcohol exposure includes deficits in discrimination and reversal learning, but traditional experimental approaches make it difficult to distinguish the effect of alcohol on discrimination learning from the effect of alcohol on reversal learning. Young rhesus macaques can be used to model some aspects of human adolescence because of their anatomical, neurophysiological, and cognitive similarities with humans. Methods Adolescent male rhesus monkeys (n = 10) were trained to respond to visual stimuli on touch‐sensitive LCD panels controlled by the nonhuman primate version of CANTAB software. Discrimination and reversal learning tasks were subsequently assessed after monkeys were allowed to consume varying amounts of ethanol (EtOH) in a flavored vehicle (vehicle only, up to 0.5 g/kg EtOH, up to 1.0 g/kg EtOH, and up to 1.5 g/kg EtOH). Results Acute exposure to EtOH reduced perseverance, increased response accuracy, and reduced errors during reversal learning when the task was completed within 90 minutes of EtOH consumption. No reduction in reversal errors was observed when EtOH was consumed 3 or 24 hours prior to reversal learning. EtOH only impaired discrimination learning when monkeys had very little previous EtOH exposure. Conclusions The temporal relationship between EtOH consumption and reversal learning was consistent with selective EtOH‐induced impairment of retrieval, but not storage, processes. This was evidenced by diminished perseverance on the previously correct stimulus leading to decreased errors to criterion.